Natural and experimental infection of streptococcus sp. in red hybrid tilapia (oreochromis sp.) and selected effective herbal prophylactics - Alshaafai, Milud Alsaid (2013)
Streptoccocosis, a septicaemic disease which is caused by Streptococcus bacteria is a major bacterial disease in tilapia due to the intensification of aquaculture and had caused significant economic losses in many countries, including Malaysia. Hence, the purpose of this study were to isolate and confirm Streptococcus agalactiae as a natural pathogen in Malaysian aquaculture and investigate the effect of different environmental parameters on the susceptibility of the Red hybrid tilapia to infection and the haematological, biochemical and histopathological responses of the fish following experimental infection. The in vitro and in vivo antimicrobial properties of herbal extracts against S. agalactiae were also studied to see whether selected herbal extracts could protect the fish from infection. To achieve the first objective, four intensive red hybrid tilapia (Oreochromis sp) grow-out farms were studied in the state of Selangor, Malaysia.From 600 fish samples collected, 410 isolates were successfully cultured and identified as β-haemolytic group B Streptococcus agalactiae using standard conventional methods, biochemical characteristic tests, Lancefield serogrouping as well as a PCR method to detect and confirm the pathogens involved in the infection. The median lethal dose (LD50) value in red hybrid tilapia injected intraperitoneally (IP) with selected S. agalactiae (strain ML333) within 120 hours was 1.5×105 cfu/ml. A series of experiments were conducted in order to determine the effects of a variety of environmental factors on the susceptibility of the red hybrid tilapia following S. agalactiae exposure. The mortality rate was significantly higher (P<0.05) in tilapia experimentally infected with S. agalactiae which were maintained at 33°C than those held at 20, 25 and 30°C; and in water of pH 6 compared to those held in more alkaline water. An experimental infection were also carried out in adult Red hybrid tilapia to determine the haematological, biochemical and pathological changes that occur during the disease. The erythrocytes counts (RBC), haemoglobin concentration (Hb) and haematocrit (PCV) of the experimentally infected tilapia decreased significantly (P<0.05) at 3, 5 and 7 dpi compared with the healthy fish. In contrast, leucocyte counts significantly increased from 4.20±1.8 (x103/μL) in the control fish to 13.2±5.5 at 7 day post infection. Experimental infection caused marked clinical sign abnormalities such as exophthalmia, lethargy, gallbladder enlargement, mucoid fecal casts and pale liver. Histopathological examinations showed marked mononuclear cell infiltration, congestion and haemorrhages in the spleen, liver, kidney, brain and heart tissues. In the present study, water extracts of ten herbs were screened to identify whether they have antimicrobial activities against S. agalactiae using the disk diffusion assay. The water extracts of Cinnamomum verum, Allium sativum, Syzygium aromaticum and Thymus vulgaris displayed antimicrobial properties. The minimum inhibitory concentration (MIC) values for herbal extracts were also determined by utilizing agar diffusion method. The lowest MIC value with high efficacy against S. agalactiae was 150 μg/ml, which was obtained from C. verum extract. The in vivo antimicrobial effect of C. verum was then tested by feeding tilapia fingerlings with feed supplemented with different ratios of C. verum bark extract and bark powder for 7 days before challenging with 0.1 ml of LD50 concentration (1.5×105 cfu/ml) of S. agalactiae via intraperitoneal injection. The cumulative mortality was significantly lower (P<0.05) in the fish fed on feed supplemented with C. verum extract with a ratio of 3:26 (w/w) as compared to other groups. The findings obtained in this study indicated that S. agalactiae infection has become an important health issue in tilapia farms. This study demonstrated that environmental changes increase the susceptibility of the Red hybrid tilapia to S. agalactiae infection. Results from haematological, biochemical and histological studies provided valuable and previously unknown information on the extensity of pathology associated with streptococcosis in cultured Red hybrid tilapia. This study also showed that antimicrobial properties of C. verum extract could be used as an alternative biomedicine for prophylaxis against streptococcosis.